DISEÑO DE UN PROGRAMA DE EDUCACIÓN Y CULTURA FINANCIERA PARA LA PARROQUIA “LOS ENCUENTROS” DEL CANTÓN YANTZAZA - Avila Vicente, Jhoana Abigail (2019)
The present thesis work entitled: Design of a program of education and financial culture for the parish "Los Encuentros" of Yantzaza canton, was developed in order to contribute to the progress and development of the parish by providing knowledge and tools to villagers so that they can make better financial decisions, thus was set as the main objective to design a program of education and financial culture for the parish "Los Encuentros" of Yantzaza canton, in order to prevent the misuse of money, and in turn strengthen the habit of saving to ensure the population economic stability. In this sense, the more information people obtain, the better the use of financial services and instruments. In this context, in order to meet the first objective, the information was collected through the application of surveys in order to assess the level of education and financial culture of the inhabitants. On the basis of the diagnosis obtained, the second objective was fulfilled, which consists of defining the main thematic contents with their respective participative-constructive methodology for the training program, which helps to make participants aware of the importance of properly managing their personal finances. To this end, a training plan was designed that is composed of three modules, each of which is subdivided into units: Module 1 "Generalities", where it will be known in a general way that consists of education, financial culture and financial products, Module 2 "Define our financial planning", developed with topics such as: financial planning and family budget, Module 3 "What to do with our surplus money", composed of two units such as: Investment and Savings. For the development of the third objective, a pilot test of the training process was carried out in a certain sector of the population, which was considered to be carried out with the children, since in them it is possible to educate society, being more likely to retain the attitudes and knowledge necessary to generate changes since they are the social and economic actors in the present and the future. Through training, the children were able to reflect on the new information they have received and how they would use it in their daily lives, since it will influence the development of their personal well-being and that of the community. 5 From the results of the surveys of the research process it was determined that in the parish "Los Encuentros" there is financial illiteracy due to the fact that people do not have the knowledge and financial skills having erroneous practices of this nature such as excessive expenses, inadequate administration of financial resources, which means that individuals do not progress financially and do not contribute to the development of the parish, is for them that according to the findings is considered one of the reasons for the lack of training to inculcate the habit of saving children, these being the builders of hope to culturalize society. At the end of the piloting with the students of the Educational Unit of the Millennium the delivery of piggy banks elaborated of recyclable material as plastic bottles and fomix was made, with the purpose of promoting the saving from the early age; in the same way the delivery of a plan of qualification to the rector of the Educational Unit was made so that it is considered in the study plan.